Învățarea și educația adulților unele experiențe internaționale [Articol] - Guţu, Vladimir (Tipografia „Print Caro”, 2021)
This article addresses the issue of adult learning and education in different countries and from different perspectives: organizational, structural, content. The emphasis is on the analysis of experiences and traditions of adult education in Germany, Great Britain, Denmark, Romania and the identification of development trends in this sector of education. It should be mentioned that the analysis is performed in the context of lifelong learning.
Keywords: formarea profesională; educația adulților